TRANSFORMASI AKUNTABILITAS PUBLIK DI ERA DIGITAL: ANALISIS KUALITATIF ATAS IMPLEMENTASI SISTEM INFORMASI PEMERINTAHAN BERBASIS ELEKTRONIK (SPBE) DALAM PENGELOLAAN KEUANGAN DAERAH KABUPATEN SIDOARJO - Fitri Komariyah; Amin Sadiqin; Hendra Dwi Prasetyo (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study aims to analyze the implementation of the Electronic-Based Government System (SPBE) in regional financial management in Sidoarjo Regency and its implications for the transformation of public accountability in the digital era. The research employed a qualitative method with a descriptive approach. Data were collected through interviews, observation, and documentation, then analyzed using an interactive analysis technique consisting of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of SPBE has encouraged changes in regional financial governance to become more systematic, well-documented, and data-based. SPBE contributes to improved process traceability, data consistency, monitoring efficiency, and the preparation of financial reports. However, the implementation has not been fully optimal due to several constraints, including limited human resource competence, suboptimal inter-system integration, a bureaucratic work culture still adapting to digital systems, and technical operational obstacles. This study concludes that SPBE plays an important role in promoting the transformation of public accountability, although the resulting accountability remains more dominant in internal administrative dimensions than in participatory public accountability. Therefore, stronger system integration, improved government personnel capacity, and broader public access to information are necessary.